Kritik Sosial pada Naskah Drama Musikal Calon Arang Karya Dolfry Inda Suri - Rahmadayani Rahmadayani; Nur Kholifah Palaloi (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research aims to determine the social criticism contained in the drama script "Musikal Candidate Arang" by Dolfry Indwa Suri. This research uses a qualitative descriptive method with an objective approach as the approach. The stages carried out in preparing this research, the researcher read the drama script "Musikal Calon Arang" by Dolfry Inda Suri first, then the researcher analyzed the intrinsic elements. Then the researcher categorized the parts of the drama script that referred to aspects of social criticism. The results of this research found that there is social criticism in aspects of crime, namely 1) abuse of power and 2) punishment and justice.